Working Poor: is the Safety Factor Big? - Radaev, Vadim (Journal of Economic Sociology, 2010)
Among the new poverty groups there is one, which remains in the shade, comprises from those having a job but not having enough means of subsistence. How we got this situation? What difficulties do the working poor face with and how do they try to tackle them? Why don’t they leave their permanent low-paid jobs and how large is the safety factor? The survey conducted in 1999 in four Russian cities (Moscow, Nijni Novgorod, Ekaterinburg and Krasnodar) helps to answer all these questions. 258 of working poor were asked to fill out the questionnaire during the survey, 32 deep interviews were also taken from these people (the same number in every city).